KONSEP DASAR PROFESI GURU PAI DALAM PERSPEKTIF PENDIDIKAN ISLAM KONTEMPORER - Deko Rio Putra; Bety Nurfadilah; Suris Marshanda; Alpin Sauri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The teaching profession is one of the fields of work that demands specific expertise, advanced education, and professional conduct to shape a high-quality younger generation. This paper elucidates the concepts of the teaching profession and teacher professionalism, with a focus on the context of Islamic Religious Education (PAI), including the required competency standards and the legal foundations governing it in Indonesia. Through an analysis of Law No. 14 of 2005 on Teachers and Lecturers, the competencies of PAI teachers are summarized into four main categories: pedagogical, personality, social, and professional. This legal framework provides legitimate recognition and protection for educators, although challenges persist, such as inequalities in welfare for non-permanent teachers. This discussion highlights the urgency of strengthening professionalism to realize the mandate of the 1945 Constitution regarding the enlightenment of national life.